Paradoxical personality and academic achievement in college students from Buenos Aires - Freiberg Hoffmann, Agustín (2015)
This paper presents a study on paradoxical personality, defined as a distinctive feature in creative persons, developed with 350 college students from Buenos Aires. Goals aimed at describing and analysing possible significant differences of paradoxical traits in students from diverse majors representing seven different fields of study, and examining the relationship between each bipolar trait and academic achievement. The sample was composed of 7 groups (n = 50 by group) representing fields of study typically offered in public universities, Biology, Computer Science, Engineering, Law, Nutrition, Psychology, and History of Art. Analyses by career provided descriptive information about students of these majors, concerning their paradoxical personality profiles. Correlational studies verified significant associations between academic achievement and most paradoxical traits in majors such as Computer Science, Nutrition and Psychology. Results are discussed regarding practical outcomes and teaching programs.